Development of Interactive Snakes and Ladders Media to Improve Student Learning Outcomes in Elementary School - Setyaningsih, Endah; Arini , Novanita Whindi (Journal of Educational Sciences, 2025)
Students often struggle with understanding their rights and obligations in various contexts, which negatively impacts their learning outcomes. This study aimed to address this issue by developing an interactive snake and ladder game-based media tool that helps students grasp these concepts through engaging examples in daily life. The research employed the Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The interactive game was validated by media experts (96%), subject matter experts (98%), education practitioners (84%), and students. The overall validation score was 92%, qualifying it as "highly suitable." In trials, student responses were positive: small-group trials scored 92%, and large-group trials scored 91%, resulting in an overall score of 91.5% ("highly suitable"). Pre-test scores averaged 59.80%, while post-test scores improved to 87.29%, showing a significant increase of 27.49%. This indicates that the interactive snake and ladder game effectively enhances learning outcomes in Pancasila Education for fourth-grade elementary school students. The study demonstrates the potential of gamified educational tools to improve comprehension and engagement in civic education.